Innovation Management - P&G’s Experience: A Case Study in Strategic Management - Dasari, Shailendra (Prabandhan: Indian Journal of Management, 2009)
P&G a FMCG conglomerate is among the top ten companies in USA and top 15 in the world. Their products touch the lives of three billion consumers spread over 190 countries, every day. Their turnover for the year 2007-08 was US 77billion. Their core businesses are hair care, fabric care, baby care and feminine care. They have operations spread over 90 countries and own more than 38000 patents. Throughout the twentieth century, Procter & Gamble continued to prosper. The company moved into other countries, both in terms of manufacturing and product sales, becoming an international corporation. Numerous new products and brand names were introduced over time, and Procter & Gamble began branching out into new areas. The company introduced "Tide" laundry detergent in 1946, one of their major innovations and "Prell" shampoo in 1950. In 1955, Procter & Gamble began selling the first toothpaste to contain fluoride, known as "Crest". Branching out once again in 1957, the company purchased Charmin Paper Mills and began manufacturing toilet paper and other paper products. Once again focusing on laundry, Procter & Gamble began making "Downy" fabric softener in 1960(another successful innovation) and "Bounce" fabric softener sheets in 1972. One of the most revolutionary products to come out on the market was the company’s "Pampers", first test-marketed in 1961. Prior to this, disposable diapers were not popular, although Johnson & Johnson had developed a product called "Chux". Babies always wore cloth diapers, which were leaky and labor intensive to wash. Pampers simplified the diapering process.